2014
DOI: 10.1039/c3ce41868e
|View full text |Cite
|
Sign up to set email alerts
|

ZnO superstructures via oriented aggregation initiated in a block copolymer melt

Abstract: A fast and simple one pot synthesis of ZnO nano-and microparticles initiated and driven by an amino block copolymer O,O′-bis(2-aminopropyl)polypropylene glycol-block-polyethylene glycol-block-polypropylene glycol (Jeffamine®) is reported. The specific building mechanism of ZnO mesocrystals is investigated in detail using electron microscopy and diffraction methods. Mesocrystals with a complex superstructure are formed as a result of a consecutive and oriented multiple stage aggregation process: first a 0D → 1D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 44 publications
(65 reference statements)
3
17
0
Order By: Relevance
“…It shows that under the experimental conditions used in this work the coupling of interphases with the same polarity is not promoted by the polymer, but by the presence of water independently of the DMF/water ratio. As has been demonstrated elsewhere21, 22 and suggested by other authors in the literature,19b, 35 the formation of ZnO particles with twin boundaries is the result of an oriented attachment mechanism. According to Cölfen et al., oriented attachment can occur inside a polymer matrix or be directed by magnetic and electric fields, among other possibilities 36.…”
Section: Resultssupporting
confidence: 68%
See 2 more Smart Citations
“…It shows that under the experimental conditions used in this work the coupling of interphases with the same polarity is not promoted by the polymer, but by the presence of water independently of the DMF/water ratio. As has been demonstrated elsewhere21, 22 and suggested by other authors in the literature,19b, 35 the formation of ZnO particles with twin boundaries is the result of an oriented attachment mechanism. According to Cölfen et al., oriented attachment can occur inside a polymer matrix or be directed by magnetic and electric fields, among other possibilities 36.…”
Section: Resultssupporting
confidence: 68%
“…Electron diffraction at the coupled interphase (seam cut) indicated the formation of a single crystal 21. ZnO mesocrystals characterised by the presence of the same coupling interphase formed upon ultrasonication in the block co‐polymer Jeffamine R as a result of a consecutive and oriented aggregation from quantum dots to complex multiple cone symmetries 22. For these complex superstructures, it was observed that the coupling of building blocks leads to the formation of very reactive twin interphases that have the tendency to be covered by the successive growth of smaller cones 22.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2a, b, respectively. A spherical-shaped particle nature was observed in the ZnO QDs whose size was nearly 5-10 nm (image a), where slightly elongated particles with little agglomeration were also observed which may be due to the powder samples embedded on the copper-coated grid (Klaumunzer et al 2014). Whereas in the case of ZnO/starch QDs, it shows spherical-shaped particle nature but cluster-like surface morphology was observed because ZnO QDs are embedded inside the polymer-like starch matrix (image b).…”
Section: Structural Analysismentioning
confidence: 96%
“…These secondary particles seem to be agglomerated and aggregated from primary ones; they range in size from a few tens to a few hundreds of nanometers and therefore have a broad size distribution. Assuming that the secondary particles are formed from the primary ones via a mesocrystalline pathway by oriented aggregation – which is in fact well known and frequently observed for ZnO 25, 26 (but this would be a different topic) – the primary particles have to be accountable for the above‐mentioned substructure. The size distribution of the primary particles from continuous synthesis is 20.8 ± 7.8 nm (ImageJ, 100 particles), thus showing the same size range as the “batch” particles.…”
Section: Resultsmentioning
confidence: 96%